THE ECONOMIC CYCLE IN POLISH CONSTRUCTION - Gostkowska-Drzewicka, Magdalena (Ekonomika, 2014)
Abstract. The aim of this article is to determine the relation between the phases of the business cycle and changes in prices of factors of construction production. The research covers the years 1994–2012. The dataset applied in the study includes yearly data on prices of the factors of construction production in Poland. All of these data were made available by the SEKOCENBUD. The implementation of the purpose of the study required, firstly, to construct the curve of the economic cycle in the Polish construction industry and, secondly, to determine indicators of changes in the prices of construction production factors and to compare them with the curve reflecting the state of the economic cycle in the construction industry. It was based on the results of a monthly economic situation test, which are published by the Central Statistical Office in Warsaw. A record increase in the prices of production factors in construction was observed during the recovery in 2006–2007. It was caused by the intensified demand for various types of construction services. The deep slump in the construction industry was accompanied by a slight reaction of changes in the prices of construction materials and equipment to the decreasing demand in 2002–2004 and 2008–2012. The results of the study allow to conclude that changes in the prices of production factors in construction are closely related to the situation in the sector, but this relationship is particularly noticeable in the growth phase of the cycle. Key words: economic cycle, building materials and labour, plot of land, real estate